An analytical model for the control of silica grout penetration in natural groundwater systems. (November 2017) - Pedrotti, M.; Wong, C.; El Mountassir, G.; Lunn, R.J.
Highlights: First model for gelling of colloidal silica grout in natural groundwater systems. Predictive capability without the need for parameter re-calibration. Model is presented as tool for colloidal silica grout design. Model was used in a case study to design site-specific grout mixes. Abstract: Over the last three decades, colloidal silica has been investigated and more recently adopted as a low viscosity grouting technology (e.g. for grouting rock fractures within geological disposal facilities nuclear waste). The potential of colloidal silica as a favourable grouting material exists due to: its initial low viscosity; its low hydraulic conductivity after gelling (of the order of 10 −7 cm/s); the very low injection pressures required; its controllable set/gel times (from minutes to several days); the fact it is environmentally inert; its small particle size (less than hundreds of nanometres) and its cost-effectiveness. Despite the documented success of colloidal silica based grouts for hydraulic barrier formation, research has not translated into widespread industrial use. A key factor in this limited commercial uptake is the lack of a predictive model for grout gelling which controls grout penetration: whilst data are available to underpin design of a grouting campaign in laboratory conditions, little research has been done to underpin applications in natural environments. Here we develop and validate an analytical model of colloidal silica gelling in groundwaters with varying pH and background electrolyte concentrations. This paper presents an analytical model that accounts for changes in pH, electrolyte concentration, cation valency and molar mass, silica particle size and silica concentration giving predictive capability without the need for site-specific calibration. The model is validated against experimental observations for gel times of 32–766 min, the model accurately predicts the log(gel time) with an average error of 4% which corresponds to an R 2 value of 0.96. The model is then applied to a hypothetical case study to demonstrate its use in grout design, based on published in-situ groundwater data from the Olkiluoto area of Finland. The model successfully predicts the required accelerator concentration to achieve a grout gel time of approximately 50 min, taking into account the cations already present within the synthetic groundwater.